The relationship between mobile marketing and customer relationship management (CRM) - Hadadi K.; Almsafir M.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mobile marketing refers to different kinds of marketing that contain operation of mobile phone technology to achieve the target spectators. Commonly, people associate mobile marketing with SMS and MMS marketing, pay per call mobile marketing, mobile banner ads, quick response code, location based marketing, Mobile applications and mobile website design. Among the variety of mobile services, considerable attention has been dedicated to mobile marketing specifically to mobile customer relationship management services. The mobile medium is well matched to improve classical CRM as it has a great influence and interactivity and may permit the firm to improve close relationships with clients. The main objective of this research is to investigate the relationship between mobile marketing and CRM. This paper concentrates on different types of mobile marketing and CRM to investigate which type of mobile marketing has a significant relationship on which type of CRM. This research has a quantitative approach and data which is used in this research is primary data. Data were collected by distributing questionnaire among one hundred students, especially those who are in the middle of 17-18 from international high school which is located in the Klang Valley area. The result of this research shows that teenagers are more influenced by mobile banner ads and mobile applications followed by other types of mobile marketing. Mobile applications have a wealthier mobile capability than mobile web. Deep associating of mobile apps is a great occasion for each industry to improve the loyalty of their customers. The results of this research proposed some important inferences which will support marketers to produce better mobile marketing and enhance the mobile customer relationship management services. Also, this research found that there would be a brighter future for mobile advertising rather than any other types of advertising. © 2014 IEEE.